2020
DOI: 10.1136/medethics-2020-106590
|View full text |Cite
|
Sign up to set email alerts
|

Fair and equitable subject selection in concurrent COVID-19 clinical trials

Abstract: Clinical trials emerged in rapid succession as the COVID-19 pandemic created an unprecedented need for life-saving therapies. Fair and equitable subject selection in clinical trials offering investigational therapies ought to be an urgent moral concern. Subject selection determines the distribution of risks and benefits, and impacts the applicability of the study results for the larger population. While Research Ethics Committees monitor fair subject selection within each trial, no standard oversight exists fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The findings of this study should be helpful for developing clinical management strategies for infertile couples. However, there are some limitations in the present study ( Jansen et al, 2020 ; Niehus et al, 2020 ): (1) Retrospective cohort studies are always associated with selection bias issues, with selection bias being introduced, one might expect the result to be skewed in some ways. (2) In this study, our research subjects were all Chinese patients with infertility being given IVF/ICSI treatments during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study should be helpful for developing clinical management strategies for infertile couples. However, there are some limitations in the present study ( Jansen et al, 2020 ; Niehus et al, 2020 ): (1) Retrospective cohort studies are always associated with selection bias issues, with selection bias being introduced, one might expect the result to be skewed in some ways. (2) In this study, our research subjects were all Chinese patients with infertility being given IVF/ICSI treatments during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…No articles concerning enrolment in haemophilia trials were found, but two articles were identified that discussed participant selection in cystic fibrosis clinical trials with competitive enrolment [6,10] . One article specifically examined challenges in equitable subject selection for COVID-19 therapy trials [3] .…”
Section: Literature Searchmentioning
confidence: 99%
“…Of the strategies proposed and reviewed in the literature search, 'first come, first served' was a tactic that was generally not recommended, as it unfairly advantages those who can access or learn about treatments more quickly, and neither attempts to maximise benefits nor minimise harms with what limited resources are available [3,12,14] . Several of the articles reviewed explicitly stated the need to prioritise vulnerable patients or those with a medical need, indicating that protecting at-risk patients is a common priority [3,[11][12][13][14][15] . However, this may not necessarily be a consideration that carries over to clinical trials, as clinical trials have scientific aims to fulfil that scenarios involving resource allocation do not.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on single-arm and randomized treatment trials, and we assess the three main approaches to allocating trial opportunities discussed in the literature: patient choice, physician referral, and randomization/lottery. 4 All these options have strengths and challenges. Covid-19 also has several distinct features that compound existing complexities.…”
Section: Allocation Ofmentioning
confidence: 99%